Educational Policy Implementation: A Critical Overview of Education Quality Assurance Policy in Nigeria - IJAIYA, Nike Yetunde Sidiqat; BELLO, Suliya Olawepo (International Journal of Educational Management, 2025)
Policy implementation ought to be a natural follow-up of policy making. However, the dichotomy between the two in Nigeria's educational system is a matter for concern. This paper did a critical overview of factors that cause poor policy implementation in Nigeria vis-a-vis school inspection policy and the paradigm shift to Education Quality Assurance policy (EQA) in 2015. It noted that the factors that undermined school inspection in recent years including human dereliction of duty and poor funding are still there, and are working against the achievement of the vision of £QA! It also posited that internal self supervision by the school is being highly underrated in the system in favour of external evaluation whereas teachers with their qualifications and experience can become self-monitoring, self-accountable and self-propelling if empowered and challenged. It was there.fore recommended that external evaluation should be combined with internal school-based self-supervision with a detailed handbook spelling out the roles of the head teachers, other staffs and those of the external instructional supervisors as a better means of improving learning outcomes in schools.